Literatur Review Faktor-Faktor yang Mempengaruhi Kejadian Insomnia - Ila Nabila Safiroh; Dona Yanuar Agus Santoso; Livana PH; Yulia Susanti (Pelantar Press, 2026)
Insomnia sleep disorders can lead to long-term health issues if not promptly addressed and can significantly impact an individual's quality of life, including work performance and social relationships. Furthermore, it increases the risk of health problems such as depression, anxiety, cardiovascular disease, obesity, and diabetes. This review article aims to identify the factors that influence the occurrence of insomnia. This study utilizes a literature review design with a descriptive analysis technique, examining 17 journals published within the last 5 years. The search was conducted on Google Scholar using keywords such as